The new manager's tool kit : 21 things you need to know to hit the ground running - Grimme, Don.; Grimme, Sheryl (New York : American Management Association, 2009)
The New Manager's Tool Kit arms you with the fast, practical advice you need to: increase productivity, unlock hidden talent in your people, work with different types of employees, communicate effectively with your reports, diagnose problems, coach good or problematic employees, turn on teamwork, avoid burnout, eliminate conflict, and even nurture the next generation of managers.
Introduction: A Tool Kit for Today's Workplace 1 -- Part 1 Leading People 6 -- Part 2 Different Strokes 38 -- Part 3 Leader Effectiveness 78 -- Part 4 Optimizing Contributions 96 -- Part 5 Personal and Interpersonal Effectiveness 120 -- Part 6 Eliminating Conflict 178 -- Appendix A Ten Tips to Protect Against Harassment Charges 223 -- Appendix B Ten Steps to Manage Workplace Violence 227 -- Appendix C The Impending Leadership Crisis 232 -- Resource Guide-Books and Websites Organized by Tool 239.
Includes bibliographical references (p. 239-249) and index.
Keywords: Management; Supervision of employees; Management; Supervision of employees